Analisis Penerapan Psak – 102 Murabahah (Studi Kasus Pada Ksu Bmt Rahmat Syariah Kediri) - Pratiwi, Inggrid Eka; Septiarini, Dina Fitrisia (UNIVERSITAS NEGERI SURABAYA, 2014)
AbstractThe purpose of this research is to find out whether the accounting practices which include the recognition, measurement, presentation and disclosure of the murabaha transactions applied to the BMT Rahmat Syariah in accordance with PSAK 102 about accounting murabaha. The research method used is descriptive qualitative approach with this type of case study research. The Unit of analysis in this study is the accounting treatment of murabaha is applied to the BMT Rahmat Syariah. Analytical techniques used in this research is a domain analysis techniques. From the results of the research can be determined three related domains of contract i.e. the beginning of akkadian murabaha, during the process of installment and repayment. Research results can be concluded that BMT Rahmat Syariah in terms of recognition, measurement, presentation and disclosure of early contract deal not in accordance with PSAK 102. During the process of contract, in terms of the measurement of profit murabaha were in accordance with PSAK 102, but in terms of recognition, presentation, and disclosure is not in accordance with PSAK 102. Whereas in the recognition, measurement and disclosure of fines (ta'zir) is in compliance with PSAK 102 only served and which is not in accordance with PSAK 102. At the time of payment of the measurements were in accordance with PSAK 102, however, recognition, representation, and the disclosure is not in accordance with PSAK 102.